2020
DOI: 10.1093/alcalc/agaa055
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Intake Exacerbates Cardiac Dysfunction After Myocardial Infarction

Abstract: Aims Alcohol intake is a risk factor for cardiovascular diseases. This study was designed to investigate whether chronic alcohol intake affects myocardial infarction (MI)-induced cardiac remodeling and heart failure. Methods Eight-week-old male C57BL/6 mice were randomly divided into four groups: Sham group (Sham), MI plus drinking water group (MI + Vehicle), and MI plus daily alcohol intake for 6 weeks with or without gavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…On the other hand, the positive aspects should be weighed against the negative effects, such as mitochondrial dysfunction and changes in circulation, inflammatory response, oxidative stress and programmed cell death, as well as anatomical damage to the CV system, especially the heart [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the positive aspects should be weighed against the negative effects, such as mitochondrial dysfunction and changes in circulation, inflammatory response, oxidative stress and programmed cell death, as well as anatomical damage to the CV system, especially the heart [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic consumption of high-sugar carbohydrates may lead to insulin resistance, which is associated with the development of chronic inflammation, and therefore we hypothesise that these two bacteria may influence the risk of developing left bundle branch block and atrioventricular block through this mechanism. Additionally, our study identified anaerobic bacteria like Lachnospira and Rikenellaceae, which may be linked to an increased risk of arrhythmia These anaerobic bacteria break down carbohydrates and produce short-chain fatty acids (e.g., acetic acid, propionic acid, and butyric acid) and alcohols (ethanol, isopropanol, and butanol), which affect the activity of immune cells and inflammatory responses, and the various alcohols they produce are metabolised by alcohol, causing cardiomyocyte damage and death, which ultimately leads to alterations in cardiac structure and function [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the Masson's trichrome staining, all the heart samples were sectioned into 5 μm slices starting from the suture ligation site to the apex, and every 50th slices were reserved for staining. Sections were stained using a commercially available kit (#G1340, Solarbio, China) for quantification of the scar size in the heart [ 23 ]. All sections were imaged through a fluorescence microscope (AX10 imager A2/AX10 cam HRC, Zeiss).…”
Section: Methodsmentioning
confidence: 99%